(untitled) (Cardiovascular Journal, 2013)
Background: Aim of the study was to evaluate the primary procedural success of slender PCI via transradial approach using either Bare-metal stents (BMS) or Drug Eluting Stent (DES). Methods: Total 10 patients were enrolled in this very preliminary study. Among them, Male: 8 and Female: 2. Clinical presentation were Ant MI: 4 (40%), Inf. MI: 2 (20%), Angina II-III: 3 (30%), and NSTEMI: 1 (10%). Total 10 stents were deployed. Mean age were for Male: 44yrs, for Female: 55yrs . Associated CAD risk factors were Dyslipidemia, High Blood pressure, Diabetes Mellitus, Positive FH for CAD and Smoking (all male). Results: Among the study group; 9 (90%) were Dyslipidemic, 5 (50%) were hypertensive; 6 (60%) patients were Diabetic, FH 6 (6%) and 8(63%) were all male smoker. Female patients were more obese (BMI M 24: F 27) and developed CAD in advance age. Common stented territory were LAD: 5 (50%) followed by RCA: 3 (30%) and LCX: 2 (20%). Average length and diameter of stent for LAD, RCA and LCX were 3.25, 3.16, 2.5 and 21.4, 20.3, 20 respectively. Stent used: BMS 3 (30%), Everolimus 5 (50%), Sirolimus 1(10%) and Zotarolimus 1(0.75%). Less contrast used (49.5ml), reduced radiation exposure (4727Gym2) and less fluoroscopy time (193 sec) with overall no procedural complication were observed. Conclusion: Our study has shown that the slender PCI via radial artery with a 5F guide catheter is safe with no procedural complication. It is also associated with less radiation exposure, less fluoroscopy time, good backup support and quick mobilization of patient. DOI: http://dx.doi.org/10.3329/cardio.v5i2.14320 Cardiovasc. j. 2013; 5(2): 160-164